Precision (repeatability and reproducibility) of papillary and peripapillary vascular density measurements using optical coherence tomography angiography in children - Chen, Ruru; Liu, Xinyu; Yao, Mingyu; Zou, Zhilin; Chen, Xinyi; Li, Zheng; Chen, Xin; Su, Mengjuan; Lian, Hengli; Lu, Weiwei; Yang, Yizhou; McAlinden, Colm; et al. (Frontiers in Medicine, 2023)
Importance Optical coherence tomography angiography (OCTA) has been widely applied into children, however, few studies have assessed the repeatability and reproducibility of papillary and peripapillary VD in healthy children. Objective To assess the precision of papillary and peripapillary vascular density (VD) measurements using optical coherence tomography angiography (OCTA) and analyze the effects of the signal strength index (SSI) and axial length (AL) on precision estimates. Design, setting, and participants This was a prospective observational study. Seventy-eight children aged 6–16 years underwent 4.5 × 4.5 mm OCTA (RTVue XR Avanti) disc scans: two scans by one examiner (repeatability) and two additional scans by another examiner (reproducibility). Within-subject standard deviation (Sw), test-retest reproducibility (TRT), within-subject coefficient of variation (CoV), intraclass correlation coefficient (ICC), and Bland–Altman analysis were performed. Main outcomes and measures In repeatability measurement, the fluctuation ranges (minimum to maximum) of VD between intraexaminer A/B in Sw, TRT, CoV, and ICC were (1.05–2.17)% / (1.16–2.32)%, (2.9–6)% / (3.21–6.44)%, (1.9–4.47)% / (2.08–5)%, and (0.588–0.783)% / (0.633–0.803)%, respectively. In reproducibility measurement, the fluctuation ranges of VD in Sw, TRT, CoV, and ICC were 1.11–2.13%, 3.07–5.91%, 1.99–4.41%, and 0.644–0.777%, respectively. VD was negatively correlated with SSI in most sectors of the peripapillary (e.g., inferior nasal, temporal inferior, temporal superior, superior temporal, and superior nasal). AL was positively correlated with inferior temporal VD and negatively correlated with superior nasal VD. Conclusion and relevance Optical coherence tomography angiography showed moderate-to-good repeatability and reproducibility for papillary and peripapillary perfusion measurements in healthy children. The SSI value affects most of the peripapillary VD, while AL affects only the temporal inferior and nasal superior peripapillary VD.